IMPLEMENTATION OF RAPID SAND FILTER FOR GROUNDWATER TREATMENT IN KULIM TENAYAN RAYA, PEKANBARU - Yohanna Lilis Handayani; Bambang Sujatmoko; Sigit Sutikno (Jurnal Sinergitas PKM & CSR, 2017)
The problem of the groundwater in the peat areas is the low acidity (pH) and the high content of organic matter (KMnO4). One of the relatively simple water treatment methods is to use rapid sand filter. The purpose of this community service activity is to socialize and apply rapid sand filter technology to farmer group in Kulim, Tenayan Raya, Pekanbaru. The method of socialization to farmer groups is done by making and installing rapid sand filter equipment in the location, water quality test and counseling about rapid sand filter technology. As a result, 4 rapid sand filter have been built and installed in 3 locations. Based on the parameters of pH, color and odor, the organic content of ground water quality in the area is not in accordance with the quality of clean water. The water quality after being processed in rapid sand filter has increased quality based on pH, color, odor, and KMnO4 parameters test.Keywords: peat water, rapid sand filter, water quality